Effect of the COVID‐19 pandemic on the frequency of emergency department visits in Portugal: An interrupted time series analysis until July 2021 - Sílvia Lopes; Patrícia Soares; Joana Santos Sousa; João Victor Rocha; Paulo Boto; Rui Santana (Journal of the American College of Emergency Physicians Open)
Abstract Objectives This study aims to evaluate the effect of the COVID‐19 pandemic on the frequency of emergency department (ED) visits in Portugal between March 2020 and July 2021. Methods We used data on the monthly number of visits for all public hospitals’ EDs from mainland Portugal between January 2017 and July 2021. We studied the impact of the pandemic overall, by type of ED (general, pediatric, and obstetric) and by Manchester Triage System color (red, orange, yellow, green, and blue) using an interrupted time series analysis. The prepandemic period corresponded to the months from January 2017 to February 2020 and the pandemic period to the months from March 2020 to July 2021. Results We observed over 26 million ED visits, the majority in general EDs (74.0%) and triaged yellow (48.4%) or green (38.4%). During the pandemic period, ED visits decreased 45.7% (95% confidence interval [CI]: –39.8% to –51.2%) and pediatric ED visits decreased by 72.4% (95% CI: –64.6% to –78.6%). A decrease was observed for all colors but tended to be progressively smaller as the priority increased. There was an increase in ED visits during the pandemic period (2.3%; 95% CI: 1.4% to 3.2%), eventually returning to prepandemic values. Conclusion Our data indicate a considerable and long‐lasting effect of the COVID‐19 pandemic affecting mainly pediatric and milder cases, which were returning toward prepandemic values as the pandemic progressed. In a country with frequent use of EDs, the health system may need to be prepared to respond to prepandemic baseline ED demand, together with additional demand because of long‐term sequels of COVID‐19 cases and delayed care for chronic and acute conditions.